Anal Incontinence after Anterior Rectum Resection in Cancer Patients - O. I. Kit; E. N. Kolesnikov; M. A. Averkin; S. V. Sanamyants; A. V. Snezhko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To study the functioning of the anal sphincter after performing anterior rectum resection in cancer patients.Materials and methods. The anal sphincter function was studied in 144 patients with colorectal cancer, equally in 72 men and 72 women. The study was carried out at the Rostov Cancer Research Institute. All patients underwent R0 anterior rectum resection with the total mesorectumectomy and the formation of a preventive ileostomy. An assessment of the retention function was performed by sphincterometry using a manometric complex with a nonperfusion water-filling sensor according to the generally accepted method.Results. Disturbances in the normal functioning of the sphincter were noted in 24 (16.7 %) patients. The use of sphincterometry allowed disturbances in the functioning of the internal and external anal sphincters in men and women to be identified, along with differences between the groups. The results indicate a higher incidence of anal incontinence (AI) in women compared to men (t ≥ 2, the differences are significant). In addition, patients with a lower localisation of the anastomosis demonstrated a higher incidence of AI and more pronounced AI manifestations.Conclusions. The obtained data on the functioning of the anal sphincter after anterior rectum resection in cancer patients indicate gender differences in the incidence of late complications after surgery, as well as the importance of taking into account the localisation of the tumour for selecting an adequate amount of surgical intervention.